Chelation Therapy Associated with Antioxidant Supplementation Can Decrease Oxidative Stress and Inflammation in Multiple Sclerosis: Preliminary Results - Alessandra Vezzoli; Simona Mrakic-Sposta; Cinzia Dellanoce; Michela Montorsi; Daniele Vietti; Maria Elena Ferrero (MDPI AG, 2023)
An imbalance of oxy-inflammation status has been involved in axonal damage and demyelination in multiple sclerosis (MS). The aim of this study was to investigate the efficacy of an antioxidant treatment (calcium disodium ethylenediaminetetracetic acid-EDTA) chelation therapy associated with a micronutrient complex in MS patients. A total of 20 MS patients and 20 healthy subjects, enrolled as a control group (CTR), were recruited. We measured the plasma ROS production and total antioxidant capacity (TAC) by a direct assessment using Electron Paramagnetic Resonance; activities of the antioxidant system (thiols' redox status and enzymes); and the urinary presence of biomarkers of oxidative stress by immunoenzymatic assays. We also evaluated the levels of inflammation by plasmatic cytokines (TNFα, IL-1β, and IL-6) and assessed the sICAM levels, as well as the nitric oxide (NO) catabolism and transthyretin (TTR) concentration. Comparing CTR and MS, in the latter ROS production, oxidative damage, inflammatory biomarkers, and NO metabolite concentrations results were significantly higher, while TAC was significantly lower. Treatment in MS induced significant (p < 0.05) down-regulating of pro-inflammatory sICAM1, TNF-α, IL6, as well as biomarkers of lipid peroxidation and DNA damage production. The protective effect exhibited may occur by decreasing ROS production and increasing antioxidant capacity, turning into a more reduced thiols' status.